2010
DOI: 10.1167/iovs.09-4862
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sildenafil and Tadalafil on Intraocular Pressure in Sheep: Implications for Aqueous Humor Dynamics

Abstract: These data are consistent with a vasodilator-evoked increase in plasma-like fluid in the AC, which likely accounts for the IOP elevation. The results are discussed with a model for AH dynamics that may be of importance to senior individuals treated for vascular diseases with these compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 18 publications
3
29
0
Order By: Relevance
“…There are quite a few studies using applanation tonometry in animals (Priehs et al, 1990;Miller et al, 1990;Miller et al, 1991;Dziezyc et al, 1992;Passaglia et al, 2004;Candia et al, 2010;Gerometta et al, 2010;Ribeiro et al, 2010;Rusanen et al, 2010), but we found no reports on the assessment of the mean IOP in healthy sheep using the applanation tonometer Tonopen XL e . The purpose of this study was to determine the mean IOP in healthy adult sheep using applanation tonometry with Tonopen XL e .…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…There are quite a few studies using applanation tonometry in animals (Priehs et al, 1990;Miller et al, 1990;Miller et al, 1991;Dziezyc et al, 1992;Passaglia et al, 2004;Candia et al, 2010;Gerometta et al, 2010;Ribeiro et al, 2010;Rusanen et al, 2010), but we found no reports on the assessment of the mean IOP in healthy sheep using the applanation tonometer Tonopen XL e . The purpose of this study was to determine the mean IOP in healthy adult sheep using applanation tonometry with Tonopen XL e .…”
Section: Introductionmentioning
confidence: 61%
“…The MacKay-Marg applanation tonometer, which is considered the golden standard in Veterinary Medicine, has no longer been manufactured. A portable Mackay-Marg-type tonometer (Tonopen) has been widely used among veterinary ophthalmologists and has been assessed in dogs, cats, horses, and in some extent in sheep (Miller et al, 1990;Priehs et al, 1990;Miller et al, 1991;Dziezyc et al, 1992;Passaglia et al, 2004;Candia et al, 2010;Gerometta et al, 2010;Rusanen et al, 2010); however, a controlled study measuring the baseline IOP in healthy sheep, using applanation tonometry with Tonopen XL e , has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Later studies were made on felines (Gonçalves et al 2005), rabbits (Liu et al 2007) and sheep (Gerometta et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature contained anecdotal reports observing an elevated IOP in senior patients (older than 70 years of age) who had taken sildenafil (Yajima et al, 2000). Because of the possibility that potent PDE5 inhibitors may increase IOP in a particular group of individuals, we recently tested the effects of sildenafil (and tadalafil, a longer lasting PDE5 inhibitor) on the IOP of a sheep animal model (Gerometta et al, 2010) Sheep were used because of the similarity to humans for their ocular response to topical glucocorticosteroid instillations and resulting ocular hypertension (Gerometta et al, 2009), which occurs due to a reduction in conventional outflow facility (Candia et al, 2010). Sheep also exhibited a robust increase in IOP one hour after oral ingestion of either sildenafil (50 and 100 mg) or tadalafil (20 mg).…”
Section: Introductionmentioning
confidence: 99%
“…Sheep also exhibited a robust increase in IOP one hour after oral ingestion of either sildenafil (50 and 100 mg) or tadalafil (20 mg). We earlier discussed in detail a potential model to explain the IOP rise secondary to sildenafil treatment (Gerometta et al, 2010). …”
Section: Introductionmentioning
confidence: 99%